2014
DOI: 10.1155/2014/589712
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Phosphide Poisoning

Abstract: Zinc phosphide has been used widely as a rodenticide. Upon ingestion, it gets converted to phosphine gas in the body, which is subsequently absorbed into the bloodstream through the stomach and the intestines and gets captured by the liver and the lungs. Phosphine gas produces various metabolic and nonmetabolic toxic effects. Clinical symptoms are circulatory collapse, hypotension, shock symptoms, myocarditis, pericarditis, acute pulmonary edema, and congestive heart failure. In this case presentation, we aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…Mostly the victims succumbed despite of fluid resuscitation, inotropic support, renal replacement or bicarbonate therapy [3]. Ozgur et al, had reported another 22 year old patient who expired following severe refractory acute pulmonary oedema with renal as well as liver impairment, myopericarditis leading to refractory acidosis and respiratory arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly the victims succumbed despite of fluid resuscitation, inotropic support, renal replacement or bicarbonate therapy [3]. Ozgur et al, had reported another 22 year old patient who expired following severe refractory acute pulmonary oedema with renal as well as liver impairment, myopericarditis leading to refractory acidosis and respiratory arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphine mainly affects the cardiovascular, respiratory, gastrointestinal (GI), hepatobiliary, and hematologic systems and causes electrolyte and metabolic abnormalities 1,2. The severe clinical symptoms in patients with phosphine poisoning include circulatory collapse, hypotension, pulmonary edema, congestive heart failure, cardiac arrhythmia, and acute renal failure 1,3,4. No specific antidote has been identified; therefore, the main treatment is supportive care.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc phosphide (Zn 3 P 2 /ZnP) is used as a highly effective rodenticide to protect grain from rodents and is usually produced as a dark gray powder [1]. When ingested by accident, through suicidal or homicidal attempts, in the presence of water and acid in the stomach, it transforms into phosphine gas (PH 3 ) and affects different parts of the body especially the heart, liver, and lungs.…”
Section: Introductionmentioning
confidence: 99%
“…When ingested by accident, through suicidal or homicidal attempts, in the presence of water and acid in the stomach, it transforms into phosphine gas (PH 3 ) and affects different parts of the body especially the heart, liver, and lungs. Till date, there is no known specific antidote [1]. The estimated mortality rate of ZnP poisoning is around 37-100% [2].…”
Section: Introductionmentioning
confidence: 99%